The length of the G1 phase is an essential determinant of H3K27me3 landscapes across diverse cell types. - Abby Trouth; Kameswaran Ravichandran; Philip R Gafken; Sara Martire; Gabriel E Boyle; Giovana M B Veronezi; Van La; Stephanie J Namciu; Laura A Banaszynski; Jay F Sarthy; Srinivas Ramachandran (PLoS Biology)
Stem cells have lower facultative heterochromatin as defined by trimethylation of histone H3 lysine 27 (H3K27me3) compared to differentiated cells. However, the mechanisms underlying these differential H3K27me3 levels remain elusive. Because H3K27me3 levels are diluted 2-fold in every round of replication and then restored through the rest of the cell cycle, we reasoned that the cell cycle length could be a key regulator of total H3K27me3 levels. Here, we propose that a short G1 phase restricts H3K27me3 levels in stem cells. To test this model, we determined changes to H3K27me3 levels in mouse embryonic stem cells (mESCs) globally and at specific loci upon G1 phase lengthening - accomplished by thymidine block or growth in the absence of serum (with the "2i medium"). H3K27me3 levels in mESCs increase with G1 arrest when grown in serum and in 2i medium. Additionally, we observed via CUT&RUN and ChIP-seq that regions that gain H3K27me3 in G1 arrest and 2i media overlap, supporting our model of G1 length as a critical regulator of the stem cell epigenome. Furthermore, we demonstrate the inverse effect - that G1 shortening in differentiated human HEK293 cells results in a loss of H3K27me3 levels. Finally, in human tumor cells with extreme H3K27me3 loss, lengthening of the G1 phase leads to H3K27me3 recovery despite the presence of the dominant negative, sub-stoichiometric H3K27M mutation. Our results indicate that G1 length is an essential determinant of H3K27me3 landscapes across diverse cell types.